Organisational citizenship behaviour and effective organisational performance: a case study - Chew, Kenneth Han Ming (2018)
In an increasingly competitive and globalised world, it has become crucial for organisations to have committed workforce that are willing to embrace change and collectively drive the organisation forward. The current trend where organisations emphasise the use of teams and exceptional service quality has increased the need for employees to be more independent and productive. Against this context, organisational citizenship behaviours (OCB) have been recognised as a valuable element of success for organisations. This study aims to identify how OCB is able to influence the effective organisational performance in an organisation undergoing a major corporate restructuring. OCB in this study is measured by altruism, civic virtue and sportsmanship, being the three OCB variables that can best influence quality of service in service organisations (Yoon & Suh, 2003). Primary data were gathered from 162 employees of a large diversified multinational company and were complemented with discussions with three managers to provide more meaningful understanding of the company’s efforts. The study found that all three studied variables of OCB, namely altruism, civic virtue and sportsmanship, had significant positive relationships with organisational performance. Among the three OCB variables, sportsmanship was found to have the strongest influence towards organisational performance in an organisation undergoing a major corporate restructuring, followed by altruism and civic virtue. Consistent organisational performance can be realised through the effective facilitation of citizenship behaviours. The study did not find any significant difference between employees of different gender and job grades, and their perception towards organisational performance. Four integrated recommendations to increase effective organisational performance with a focus on supporting OCB during periods of change were suggested. The recommendations were to adopt an organic organisational structure, move towards continuous feedback and qualitative employee assessment performance management systems, encourage transformational leadership and inculcate management citizenship behaviours. The successful facilitation of OCB can form a source of sustainable competitive advantage that is difficult to be imitated by competitors.